2019
DOI: 10.1002/jcb.28915
|View full text |Cite
|
Sign up to set email alerts
|

β‐Elemene suppresses the proliferation of human airway granulation fibroblasts via attenuation of TGF‐β/Smad signaling pathway

Abstract: Background Benign airway stenosis is easily to recur as a result of hyperplastic airway granulation tissues. Our previous study proved that a Chinese drug, β‐elemene, could inhibit the proliferation of fibroblasts cultured from these tissues, which could decrease the recurrence rate of this disease. Methods To find out the mechanism for this effect, we first cultured normal human airway fibroblasts and human airway granulation fibroblasts with different concentrations of β‐elemene for the same time or the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…Our findings revealed that β-elemene can inhibit the proliferation of PHEGFs and induce their apoptosis in a concentration-dependent manner. This finding is in line with previous research indicating that β-elemene has the ability to suppress the proliferation of tracheal granulation fibroblasts and mitigate airway stenosis [ 36 , 37 ]. The PI3K/AKT signaling pathway, a classic intracellular signal transduction pathway, governs diverse biological processes, including cell survival, apoptosis, migration, proliferation, and inflammatory responses [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings revealed that β-elemene can inhibit the proliferation of PHEGFs and induce their apoptosis in a concentration-dependent manner. This finding is in line with previous research indicating that β-elemene has the ability to suppress the proliferation of tracheal granulation fibroblasts and mitigate airway stenosis [ 36 , 37 ]. The PI3K/AKT signaling pathway, a classic intracellular signal transduction pathway, governs diverse biological processes, including cell survival, apoptosis, migration, proliferation, and inflammatory responses [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…It should also be noted that there may exist other regulatory mechanisms underlying the effect of β-elemene on fibroblasts. Xue et al suggested that β-elemene attenuated the proliferation of human airway granulation fibroblasts through suppressing the TGF-beta/Smad signaling pathway . Another study, although it corroborates our study in regard to the p38MAPK signaling pathway, indicated that β-elemene functioned as a trigger for apoptosis of human rheumatoid arthritis fibroblast-like synoviocytes through reactive oxygen species-dependent activation of p38MAPK .…”
Section: Discussionsupporting
confidence: 88%
“…Xue et al suggested that β-elemene attenuated the proliferation of human airway granulation fibroblasts through suppressing the TGF-beta/Smad signaling pathway. 25 Another study, although it corroborates our study in regard to the p38MAPK signaling pathway, indicated that βelemene functioned as a trigger for apoptosis of human rheumatoid arthritis fibroblast-like synoviocytes through reactive oxygen species-dependent activation of p38MAPK. 20 Herein, the complex mechanistic actions by which β-elemene modulates fibroblasts merit further investigations.…”
Section: Discussionsupporting
confidence: 87%
“…It has been found that TGF-β1 is overexpressed in benign airway stenosis [ 12 , 33 ]. The levels of Smad2 and Smad3 have also been shown to increase in human airway granulation fibroblasts in vitro [ 34 ]. In the present study, TGF-β1 protein levels were elevated in TS rats, and this effect was attenuated by PLB.…”
Section: Discussionmentioning
confidence: 99%